Pemanfaatan Ecobrick dari Botol Bekas untuk Tugu Tulisan di Toapaya Selatan: Solusi Ramah Lingkungan - Samuel Crisna Prandaka; Ragil Wahyu Ramadhan; Indah Pertiwi; Hidayah Andreani; Zaria Tasya; Putri Azzahra; Ponita Ponita; Agusmawati Alya Putri; Marcel Wangnandra; Nur Asma Riani Siregar (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Plastic waste pollution has become an increasingly complex environmental challenge, especially in coastal areas and islands such as the Riau Islands Province. South Toapaya Village, located in Bintan Regency, faces serious problems related to waste accumulation, especially plastic, originating from household activities and waste flows from surrounding areas. This situation is exacerbated by a waste management system that is still limited, fragmented, and not yet fully sustainable. This article explores the potential of ecobricks as an innovative community-based approach to address this pressing issue. Ecobrick plastic bottles filled with clean, dry inorganic waste offer a simple yet effective strategy to reduce waste while producing modular building materials. The main focus of this study is the application of ecobricks in the construction of village landmark monuments, which are expected to become symbolic markers of local identity. This approach not only offers a technical solution to plastic pollution but also serves as a means to strengthen cultural identity and encourage collective community participation. The success of this initiative depends on continuous education, intensive socialization, and cross-sector collaboration. In this way, the project is expected to generate ecological and social benefits simultaneously, contributing to sustainable rural development in the region.